2015
DOI: 10.1200/jco.2014.57.4756
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo-Like Depigmentation in Patients With Stage III-IV Melanoma Receiving Immunotherapy and Its Association With Survival: A Systematic Review and Meta-Analysis

Abstract: Although vitiligo occurs only in a low percentage of patients with melanoma treated with immunotherapy, our findings suggest clear survival benefit in these patients. Awareness of vitiligo induction in patients with melanoma is important as an indicator of robust antimelanoma immunity and associated improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
379
2
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(416 citation statements)
references
References 136 publications
26
379
2
9
Order By: Relevance
“…4,5,7,8 An association between appearance of skin irAEs and OS in melanoma has been reported. [13][14][15]17 Similarly, our data suggest an association between skin irAEs and tumor response. The histological analysis of the rashes on the one hand allowed us to rule out clinical differential diagnoses of eczema and psoriasis and on the other hand revealed that the rashes were characterized by an inflammation rich in CD3C T-lymphocytes.…”
Section: Discussionmentioning
confidence: 48%
“…4,5,7,8 An association between appearance of skin irAEs and OS in melanoma has been reported. [13][14][15]17 Similarly, our data suggest an association between skin irAEs and tumor response. The histological analysis of the rashes on the one hand allowed us to rule out clinical differential diagnoses of eczema and psoriasis and on the other hand revealed that the rashes were characterized by an inflammation rich in CD3C T-lymphocytes.…”
Section: Discussionmentioning
confidence: 48%
“…Biomarker studies of tumor biopsies have identified tumor and immune markers predictive of beneficial anti-tumor responses to checkpoint therapy 68 , including PD-L1 expression on tumor cells and CD8 + T cell infiltration of the TME. The occurrence of autoimmune skin depigmentation (vitiligo) after immunotherapy with a variety of modalities is associated with improved long-term survival 69 . In addition, the typical kinetics of the onset of immunotoxicity have been described for some therapies, including ipilimumab, in which skin conditions are typically seen as the first manifestation, followed by colitis, and later, hepatitis and polyendocrinopathies 70 .…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…However, symptoms on an average start 3-4 weeks after treatment. Vitiligo has also been reported [19,20] (Figure 2). In severe cases, toxic epidermal necrolysis and Stevens-Johnson syndrome can occur, but in less than 1% of patients [15,19].…”
Section: Dermatologicalmentioning
confidence: 92%
“…Vitiligo may be associated with clinical beneit. Although it occurs in a small percentage of patients undergoing immunotherapy, there is a clear survival beneit in patients who do develop vitiligo during treatment [19,20]. In some patients, vitiligo is associated with long-term survival [19,20].…”
Section: Managementmentioning
confidence: 99%